Identification of a Calcium Signalling Pathway of S-[6]-Gingerol in HuH-7 Cells. (17th July 2013) - Li, Xiao-Hong; McGrath, Kristine C. Y.; Tran, Van H.; Li, Yi-Ming; Mandadi, Sravan; Duke, Colin C.; Heather, Alison K.; Roufogalis, Basil D.
Abstract : Calcium signals in hepatocytes control cell growth, proliferation, and death. Members of the transient receptor potential (TRP) cation channel superfamily are candidate calcium influx channels. NF κ B activation strictly depends on calcium influx and often induces antiapoptotic genes favouring cell survival. Previously, we reported that S -[6]-gingerol is an efficacious agonist of the transient receptor potential cation channel subfamily V member 1 (TRPV1) in neurones. In this study, we tested the effect of S -[6]-gingerol on HuH-7 cells using the Fluo-4 calcium assay, RT-qPCR, transient cell transfection, and luciferase measurements. We found that S -[6]-gingerol induced a transient rise in [ Ca 2 + ] i in HuH-7 cells. The increase in [ Ca 2 + ] i induced by S -[6]-gingerol was abolished by preincubation with EGTA and was also inhibited by the TRPV1 channel antagonist capsazepine. Expression of TRPV1 in HuH-7 cells was confirmed by mRNA analysis as well as a test for increase of [ Ca 2 + ] i by TRPV1 agonist capsaicin and its inhibition by capsazepine. We found that S -[6]-gingerol induced rapid NF κ B activation through TRPV1 in HuH-7 cells. Furthermore, S -[6]-gingerol-induced NF κ B activation was dependent on the calcium gradient and TRPV1. The rapid NF κ B activation by S -[6]-gingerol was associated with an increase in mRNA levels of NF κ B-target genes: cIAP-2, XIAP, and Bcl-2 that encode antiapoptotic proteins.